Metagenomic exploration of multi-resistance genes linked to microbial attributes in active nonferrous metal(loid) tailings. (15th March 2021) - Liu, Jian-li; Yao, Jun; Zhu, Xiaozhe; Zhou, De-liang; Duran, Robert; Mihucz, Victor G.; Bashir, Safdar; Hudson-Edwards, Karen A.
Abstract: Mine tailings sites are considered as a continuous source of discharged metal(loid)s and residual organic flotation reagents. They are extremely toxic environments representing unique ecological niches for microbial communities. Mine tailings as a source of multi-resistance genes have been poorly investigated. Metagenomic analysis for four active nonferrous metal(loid) tailings sites with different environmental parameters was conducted. The abundance of Thiobacillus, able to tolerate acidity and showing iron- and sulfur/sulfide oxidation capacities, was significantly different ( p < 0.05) between acid and neutral tailings sites. Correlation analyses showed that Zn, Pb, TP, Cd, and Cu were the main drivers influencing the bacterial compositions. Multi-metal resistance genes (MRGs) and antibiotic resistance genes (ARGs), such as baca and copA, were found to be co-selected by high concentrations of metal(loid)s tailings. The main contributors to different distributions of MRGs were Thiobacillus and Nocardioides genus, while genera with low abundance (<0.1%) were the main contributors for ARGs. Functional metabolic pathways related to Fe–S metabolism, polycyclic aromatic hydrocarbons (PAHs) degradation and acid stress were largely from Altererythrobacter, Lysobacter, and Thiobacillus, respectively. Such information provides new insights on active tailings with highly toxic contaminants. Short-term metal(loid) exposure of microorganism in active nonferrous metal(loid) tailings contribute to the co-occurrence of ARGs and MRGs, and aggravation of tailings acidification. Our results recommend that the management of microorganisms involved in acid tolerance and metal/antibiotic resistance is of key importance for in-suit treatment of the continuous discharge of tailings with multiple metal(loid) contaminants into impoundments. Graphical abstract: Image 1 Highlights: Microorganism from four typical non-ferrous active tailings were investigated. MRGs and ARGs were co-selected by high concentrations of metal(loid)s tailings. Thiobacillus and Nocardioides were the main contributors of MRGs distribution. The low abundant genera (< 0.1%) were the main contributors for ARGs distribution. Short-term metal exposure contributed to the aggravation of tailings acidification.